2012
DOI: 10.1111/j.2044-8295.2011.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Men behaving nicely: Public goods as peacock tails

Abstract: Insights from sexual selection and costly signalling theory suggest that competition for females underlies men's public good contributions. We conducted two public good experiments to test this hypothesis. First, we found that men contributed more in the presence of an opposite sex audience, but there was no parallel effect for the women. In addition, men's public good contributions went up as they rated the female observer more attractive. In the second experiment, all male groups played a five round public g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 47 publications
2
89
2
1
Order By: Relevance
“…The present study provides some support for the sexual selection hypothesis that altruism and cooperation may serve as sexually selectable traits as participants behaved favorably towards the person in the attractive image, particularly among males. The reason why this effect was stronger for males is because males have been found to engage in courtship displays more than females, especially towards females they find attractive (Van Vugt & Iredale, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides some support for the sexual selection hypothesis that altruism and cooperation may serve as sexually selectable traits as participants behaved favorably towards the person in the attractive image, particularly among males. The reason why this effect was stronger for males is because males have been found to engage in courtship displays more than females, especially towards females they find attractive (Van Vugt & Iredale, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If one were to draw exclusively on the psychological literature, one might presume the former. For example, studies have found that women conform more when their mating drives are primed (Griskevicius, Goldstein, Mortensen, Cialdini, & Kenrick, 2006), that attractive women report higher levels of conformity (see Segal-Caspi, Roccas, & Sagiv, 2012), and that (unlike men) women do not try to separate themselves from the crowd in the presence of an attractive, opposite sex audience (Van Vugt & Iredale, 2013). Furthermore, men become more nonconformist after a mating prime (Griskevicius et al, 2006) and men low in agreeableness report having more casual sex (Urbaniak & Kilmann, 2006).…”
Section: A Critical Test Of the Assumption That Men Prefer Conformistmentioning
confidence: 99%
“…This idea has been discussed under the terms biological markets [6,55] and competitive altruism [35,68], and it has been empirically demonstrated that partner choice increases prosocial behaviour through competition [63,69,80]. However, whilst partner choice explains why trustees would offer a higher return, such work does not describe why an individual would reject all available profitable-but-unfair offers.…”
Section: Discussionmentioning
confidence: 99%